Degree and forms of codeswitching: Academic and social engagement impact among ESL college education students - Crystel Rivas; Kyla Miravalles; Nicole Cabarles; Isabel Bartolay; Sharmelle Garcia (Yayasan Mitra Persada Nusantara, 2026)
This study investigated language alternation, specifically code-switching and translanguaging, among second-year education students at DEBESMSCAT, analyzing its manifestations and effects on academic and social engagement. Utilizing an Explanatory Sequential mixed-methods design, the research initially quantified code-switching prevalence and forms through a comprehensive survey. Subsequently, in-depth qualitative interviews explored students' subjective experiences, language preferences, and perceived impacts on learning, understanding, and social interaction. Findings indicate that code-switching is a pervasive communicative strategy across all examined majors, functioning as both a cognitive and social resource that enhances participation and collaboration. Science and Filipino students extensively employ it for conceptual clarification in academic settings, while Social Studies students predominantly use it in informal, peer-based, and collaborative interactions. Despite its demonstrable utility in enhancing comprehension, participation, and engagement, students reported challenges in balancing practical communication practices with institutional English-only mandates, expectations, and specific academic requirements. Furthermore, language alternation was found to support confidence-building, collaborative learning, inclusivity, and positive peer relationships in diverse classroom contexts, thereby fostering deeper understanding. The study concludes that language alternation serves as an indispensable, dynamic tool fostering understanding, confidence, and peer solidarity, thereby underscoring the necessity for pedagogies that validate, support, and effectively integrate students' multilingual competencies within higher education environments.